Constraints on Fluctuating Star Formation Rates for Intermediate-mass Galaxies with Hα and UV Luminosities - Shannon G. Patel; Daniel D. Kelson; Louis E. Abramson; Zahra Sattari; Brian Lorenz (The Astrophysical Journal, 2023)
We study the recent star formation histories (SFHs) of 575 intermediate-mass galaxies (IMGs, 10 ^9 ≤ M / M _⊙ ≤ 10 ^10 ) in COSMOS at 0.3 < z < 0.4 by comparing their H α and UV luminosities. These two measurements trace star formation rates (SFRs) on different timescales and together reveal fluctuations in recent activity. We compute L _H _α from Magellan IMACS spectroscopy, while L _UV is derived from rest-frame 2800 Å photometry. Dust corrections are applied to each band independently. We compare the deviation of L _H _α and L _UV from their respective star-forming sequences (i.e., ${\rm{Δ }}logL_{{\rm{H}}α }$ and ${\rm{Δ }}logL_{UV}$ ), and after accounting for observational uncertainties we find a small intrinsic scatter between the two quantities ( σ _δ ≲ 0.03 dex). This crucial observational constraint precludes strong fluctuations in the recent SFHs of IMGs: simple linear SFH models indicate that a population of IMGs would be limited to only factors of ≲2 change in SFR over 200 Myr and ≲30% on shorter timescales of 20 Myr. No single characteristic SFH for IMGs, such as an exponentially rising/falling burst, can reproduce the individual and joint distribution of ${\rm{Δ }}logL_{{\rm{H}}α }$ and ${\rm{Δ }}logL_{UV}$ . Instead, an ensemble of SFHs is preferred. Finally, we find that IMG SFHs predicted by recent hydrodynamic simulations, in which feedback drives rapid and strong SFR fluctuations, are inconsistent with our observations.